About a boy - Grant, Hugh.; Collette, Toni.; Rosenthal, Jane, 1957-; De Niro, Robert; Epstein, Brad.; Bevan, Tim.; Fellner, Eric.; Hedges, Peter; Weitz, Chris, 1970-; Weitz, Paul, 1966-; Weisz, Rachel, 1971-; Brook, Isabel; et al. ([London?] : Universal Studios (UK) Limited, 2002)
Will is a good-looking, smooth-talking bachelor whose primary goal in life is to avoid any kind of responsibility. So he decides to invent an imaginary son in order to meet attractive single moms. Will gets a lesson about life from a bright but hopelessly geeky 12-year-old named Marcus. Now, as Will struggles to teach Marcus the art of being cool, Marcus teaches Will that you are never too cool to grow up.
Based on the book by Nick Hornby.
Dolby digital 5.1. 2.35:1 anamorphic widescreen.
Title from disc.
Video no., 903 839 9.
Special features include: Feature commentary with Chris and Paul Weitz ; making of About a boy ; deleted scenes with directors' commentary ; Badly Drawn Boy music videos ; Born in the UK -- interview with Badly Drawn Boy.
Credits: Director of photography, Remi Adefarasin ; editor, Nick Moore ; music, Badly Drawn Boy ; costume designer, Joanna Johnston ; production designer, Jim Clay.
Keywords: Bachelors -- Drama; Man-woman relationships -- Drama; Feature films; Video recordings